HADIST PENCIPTAAN PEREMPUAN DARI TULANG RUSUK (Analisis-Kritis Terhadap Pandangan Feminis) - Ryandi Ryandi (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2019)
This paper examines further the hadith about the creation of women from the ribs by displaying various related hadith texts, the men-takhrij sanad, analyzing their matan through the comments of the authoritative scholars. This is based on the assumption of feminists that the hadith is a gender bias or "mysoginist" - from the aspect of the sanad dho'if and comes from israiliyat, while the matan is contrary to the verses of the Koran (Surat an-Nisa: 1). From here it is found that in the sanad the hadith is valid, because all the rites are tsiqat. Although the hadith contains Israiliyat, it does not reduce its validity because it does not conflict with Aqeedah and the teachings of Islam. This hadith is not contrary to Qs. Nisa, verse: 1, is actually used as an explanation as found in At-Tabari, Ibn Kathir, Ar-Razi, and Thantawi. There are two views in interpreting the hadith, namely textual and metaphorical. The different ways of interpreting it are not tadhadd (contradictory) but only tanawwu '(diverse). In addition, this meaning does not necessarily make women inferior to men, because in the Islamic perspective, glory is not measured from the origin of creation. Therefore, the rejection and accusation of Muslim feminists regarding the hadith is wrong.